Species richness and intraspecific variation interactively shape marine diatom community functioning - Patrick K. Thomas; Marrit Jacob; Esteban Acevedo‐Trejos; Helmut Hillebrand; Maren Striebel (Limnology and Oceanography Letters)
Abstract Biodiversity generally increases productivity in ecosystems; however, this is mediated by the specific functional traits that come with biodiversity loss or gain and how these traits interact with environmental conditions. Most biodiversity studies evaluate the effects of species richness alone, despite our increasing understanding that intraspecific diversity can have equally strong impacts. Here, we manipulate both species richness and intraspecific richness (i.e., number of distinct strains) in marine diatom communities to explicitly test the relative importance of species and strain richness for biomass and trait diversity in six distinct temperature/nutrient environments. We show that species and strain richness both have significant effects on biomass and growth rates, but more importantly, they interact with each other, indicating that cross‐species diversity effects depend on within‐species diversity and vice versa. This intertwined relationship thus calls for more integrative approaches quantifying the relative importance of distinct biodiversity components and environmental context on ecosystem functioning.